The China price: Evidence and some implications - Alvarez, Roberto; Claro, Sebastián (Estudios de Economía, 2016)
China’s import penetration in Chilean markets is higher in unskilled-labor intensive sectors as predicted by traditional endowment-based theories of comparative advantage. However, there is also evidence of within-industry specialization. In particular, high-income countries receive higher prices for its products, and Chinese products are not only cheaper in comparison to the world average but also relative to countries with similar income per capita. These price differences cannot account for the depth and sectoral distribution of China’s import penetration. The relative price of Chinese products have stayed relatively constant since the beginning of the 1990s, which means that factors other than price, like quality upgrading, productivity growth or the access of foreign direct investment are crucial to explain the Chinese import boom.